An Advantageous Numerical Method for Solution of Linear Differential Equations by Stancu Polynomials - Acar, Neşe İşler (Trends in Computer Science and Information Technology, 2024)
In this study, a numerical method that is alternative to the Bernstein collocation method has been investigated for solution of the linear differential equations. The theory of the method has been constituted by considering the Stancu polynomials and their algebric properties. The applicability of the method has been indicated on initial and boundary value problems. In addition, the numerical results of the proposed method have been compared with the numerical results of the known method had the best approximation in the past studies. Therefore, whether usability and efficiency of the proposed method is or not has been presented. 2020 Mathematics subject classification: 41A10, 65L05, 65L10 , 65L60